2014
DOI: 10.1186/1750-1172-9-29
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of transthyretin-associated familial amyloid polyneuropathy in the Majorcan area: Son Llàtzer Hospital descriptive study

Abstract: BackgroundTransthyretin-associated Familial Amyloid Polyneuropathy (TTR-FAP) is an autosomal dominant disease caused by the deposition of abnormal transthyretin that results from a gene mutation. Although rare worldwide, there are descriptions of several endemic foci, such as in Majorca, Balearic Islands, Spain. We aimed at describing a contemporary series of TTR-FAP patients in Son Llàtzer Hospital in Majorca from an epidemiological point of view in order to report their main clinical and laboratory character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 21 publications
(35 reference statements)
2
25
0
5
Order By: Relevance
“…The mean age of onset (AO) is different depending on the endemic focus, with large variations observed across different populations. The AO in our treatment center in Mallorca has previously been reported as 50 years (Reines et al, ) , although earlier AO was observed in other regions (e.g., mean AO of 34 years in Portugal) (Sousa et al, ) .…”
Section: Introductionmentioning
confidence: 63%
“…The mean age of onset (AO) is different depending on the endemic focus, with large variations observed across different populations. The AO in our treatment center in Mallorca has previously been reported as 50 years (Reines et al, ) , although earlier AO was observed in other regions (e.g., mean AO of 34 years in Portugal) (Sousa et al, ) .…”
Section: Introductionmentioning
confidence: 63%
“…The original cases of ATTRV30M neuropathy were recorded in Portugal [1], followed by reports in Sweden and Japan [5,6] which are large endemic areas with families carrying single genetic mutations [7]. Smaller endemic foci have been reported in Majorca and Cyprus [8,9]. Recent studies have also reported late onset ATTR V30M amyloidosis cases with distinct clinical phenotype in non-endemic areas [10].…”
mentioning
confidence: 99%
“…(отмечается накопление заболевания в 2 префектурах: Arao City in Kumamoto Prefecture и Ogawa Village in Nagano Prefecture); также имеются данные для Кипра -3,72 / 100 тыс. [65]. Регионы с повышенной частотой встречаемости описаны в Испании, в частности на Балеарских островах: показатель распространенности варьирует от 5 / 100 тыс.…”
Section: распространенность эффект основателяunclassified
“…на острове Майорка до 1 / 100 тыс. на острове Менорка [65]. ТТР-САП описан и в других регионах Испании, однако число пациентов в этих районах невелико.…”
Section: распространенность эффект основателяunclassified